A‐Site Diamine Cation Anchoring Enables Efficient Charge Transfer and Suppressed Ion Migration in Bi‐Based Hybrid Perovskite Single Crystals. (24th May 2022) - Yang, Xin; Huang, Yu‐Hua; Wang, Xu‐Dong; Li, Wen‐Guang; Kuang, Dai‐Bin
Abstract: Due to the large distance or weak electronic conjugation between adjacent Bi‐I octahedrons, the charge transport in the low‐dimensional bismuth‐based hybrid perovskites is impeded and thus hinders their future developments. In this work, A‐site cation engineering by monoamine BZA (benzylamine) and diamine 3‐AMP (3‐(aminomethyl)pyridine) has been demonstrated as an efficient strategy to regulate the corresponding activation energy of ionic migration and carrier transport capacity. Given the higher polarity of 3‐AMP than BZA, producing a more efficient dielectric screening effect, it gives rise to obtaining the small exciton binding energy (50 meV) and low defect states (3.53×10 9  cm −3 ). The reduced distance of adjacent Bi‐I octahedrons by the bilateral anchoring of the 3‐AMP 2+ diamine cation enhances both electronic conjugation and charge transport performance. Therefore, the photodetector for (3‐AMP)BiI5 SC shows a 243‐fold increase in on/off ratio compared with the (BZA)3 BiI6 SC. Abstract : A‐site cation engineering is employed to regulate the dielectric screening effect in Bi‐based perovskite single crystals. The higher polarity of diamine 3‐AMP 2+ than monoamine BZA + produces a more efficient dielectric screening effect, which further reduces exciton binding energy, defect states and ion migration. As a result, the photodetector based on (3‐AMP)BiI5 single crystals achieves an excellent detection performance.